Defining disturbance in time : the ecological implications of varying temporal patterns of disturbances - Molinos, Jorge García (Trinity College (Dublin, Ireland). Department of Zoology, 2010)
Prediction and mitigation of the effects of global environmental change rely primarily on our capacity to anticipate its causes and consequences. Key to this is the ability to identify and understand the mechanisms that cause and maintain those changes. Global change models frequently predict a general tendency towards increased temporal variability of disturbance regimes. It is not entirely clear, however, how such changes will affect the effects of disturbances on ecosystem processes. This thesis explores the importance of temporal properties of disturbances for regulating the responses of ecosystems to perturbations. I followed a mechanistic experimental approach to examine, through successive laboratory and field experiments, the contribution of different temporal properties to sediment disturbance effects on stream benthic assemblages. Importantly, my experimental designs allowed me to unconfound temporal cause and effect relationships from those of other disturbance traits.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin